"Every fish in the sea is meat and so are guitarfishes": Socio-economic drivers of a guitarfish fishery in Ghana. (September 2022) - Seidu, Issah; Cabada-Blanco, Francoise; Brobbey, Lawrence K.; Asiedu, Berchie; Barnes, Paul; Seidu, Moro; Dulvy, Nicholas K.
Abstract: Rhino rays, such as guitarfishes, are increasingly targeted or retained as incidental catch and have become an economically important component in fisheries worldwide. Despite their importance, information about the catch and socioeconomics of these fisheries are virtually non-existent in West Africa. We address a significant knowledge gap about the characteristics and drivers of guitarfish fisheries in four key ray-fishing communities in the Western and Central Regions in Ghana. We conducted landing and market surveys of guitarfishes over 80 days from November 2020 to August 2021. We also interviewed 51 fishers actively involved in the guitarfish fishery across the four communities during this period using semi-structured interviews. The findings confirm the likely disappearance of sawfishes Pristis spp., as most fishers have not captured any in their lifetime. We also confirm no known catches of the African wedgefish Rhynchobatus luebberti . Our surveys documented 537 individuals from four guitarfish species across the various landing and market sites. The spineback guitarfish ( Rhinobatos irvinei ) was the most frequently landed species comprising 71 % ( n  = 383) of all guitarfishes, with 57 % of the specimens not yet sexually mature. Most fishers (71 %) stated that catches of the two larger guitarfishes (blackchin guitarfish Glaucostegus cemiculus and common guitarfish Rhinobatos rhinobatos ) have declined by 80–90 % based on their recollection. At the same time, over half (59 %) of the fishers indicated that the catches of the smaller guitarfishes (spineback guitarfish and whitespotted guitarfish Rhinobatos albomaculatus ) have declined by 40–60 %. The main drivers for the catch or retention of guitarfishes were for both international trade of their fins, and meat which are both traded locally (45 % of 51 fishers) and used as a source of food for local consumption (37 %). While we know high economic value drives the catch and trade of giant guitarfishes and wedgefishes, we show that this trade extends to the other guitarfish species. The interviews and contemporary pattern of catches are consistent with a serial depletion of rhino rays from the largest, most valuable species to the remaining smaller-bodied, less valuable guitarfishes. We recommend the development of national regulations for their protection complemented by education programs to ensure that fishers are aware of the threatened status of guitarfishes. Highlights: Fisher knowledge surveys reveal likely disappearance of sawfishes and a decline in guitarfishes in Ghana. Trade is driving fisheries for guitarfishes, as the larger rhino rays have disappeared. Guitarfish meat consumption was common among fishers in the study communities.